145 An Audit on Hip Fracture Rehabilitation Using a Community Integrated Care Programme. (16th September 2019) - Sullivan, Rachel; Khan, Sarah; Gannon, Elizabeth; Byrne, Aoife; Spencer, Michelle; Whelan, Mairin; Nee, Rory
Abstract: Background: Teiripe sa Bhaile (TsaB) is an integrated rehabilitation programme that provides Early Supported Discharge (ESD) to patients following hip fractures. It involves weekly multidisciplinary domiciliary visits to patients under the guidance of a community geriatrician. ESD in hip fractures has been proven to be safe, more effective at improving functional recovery than inpatient rehab with a reduced average length of stay (LOS) (Chudyk 2009) and better outcomes in mobility and quality of life. (Langeland 2019) Methods: A retrospective chart review was carried out on patients enrolled in TsaB since July 2018.  The Chartered Society of Physiotherapy for Hip Fracture Rehabilitation state that following discharge from hospital, rehabilitation should commence within 72 hours and all patients should receive two hours of rehabilitation per week until they have reached their goals. An appropriate outcome measure is recommended to measure progress against each rehab goal. The Functional Independence Measure (FIM) which looks at their level of assistance with Activities of Daily Living, was recorded pre and post completion of the programme. Results: Fifteen patients completed TsaB over 3 to 8 week period. The male to female ratio was 3:1. The average age was 80.75 years. The average LOS in hospital post hip fracture was 54 days. The average LOS in hospital with TsaB was 14.8 days. This equates to 4 bed days saved per week. Each patient was seen within 72 hours of referral and received on average 3 hours per week of rehabilitation until their rehabilitation goals were achieved. Average improvement in FIM was 36.35 (>20 is clinically significant). The average Rockwood frailty scale pre-rehabilitation was 5.6 (mild to moderately frail). This improved to 3.14 (managing symptoms) on discharge. No patients were readmitted within the 30 days post discharge from hospital. Conclusion: TsaB is a home based integrated rehabilitation programme that enables patients to receive rehab in their homes and reduces the likelihood of complications such as hospital acquired infections and deconditioning.